Teachers' Pedagogical Competence in Psychomotor Assessment to Improve Collaborative, Creative, Communication, Critical Thinking (4C) of Junior High School Students - Brata, Diah Puji Nali; Utomo, Edy Setiyo; Farhan, Ahmad (KnE Social Sciences, 2025)
Teachers’ professionalism has an important role in improving learning quality. The independent curriculum provides autonomy to teachers in learning and assessment. Teachers in revolution era 5.0 must be able to develop 4C skills for students’ potential sustainability. 4C competence is very important for a competitive job. Teachers’ pedagogical competence in doing assessments is essential to improve learning quality. It is a must for teachers to give learning experiences with 4C. However, teachers have not integrated the students’ 4C skills clearly in doing psychomotor assessments. The teachers have not identified the elements of 4C integrated with psychomotor assessment. It will impactthe result of psychomotor assessment, which is subjective, less valid, and less transparent. This research aims to know (1) the technique and instrument of psychomotor assessment implemented by teachers, (2) teachers’ pedagogical competence in doing psychomotor assessment integrated with 4C, and (3) teachers’ obstacles in doing psychomotor assessment integrated with 4C. The research method uses a qualitative approach. The research subjects are teachers at three public junior high schools SMPN in East Java. The research procedure consists of giving a questionnaire, doing interviews, and doing observation. The triangulation method (interview, observation, and documentation) becomes the basic element to explain the findings. The data analysis is done through data reduction, data display, and data verification. The findings show that (1) the techniques of psychomotor assessment used by teachers are the product (13%), project (16%), practice (40%), and observation (23%); most of instruments used are rubric (98%), checklist (2%). (2) Teachers’ pedagogical competence in psychomotor assessment shows that the teachers are less optimal in giving the result of psychomotor assessment to determine the learning completeness integrated with 4C, the teachers are less optimal in communicating the result of psychomotor assessment to the stakeholders, the teachers are less optimal in taking benefit from the result of psychomotor to improve the learning quality. (3) The obstacles faced by teachers in the implementation of psychomotor assessment integrated with 4C, as most of the teachers less understand the characteristics and steps of technique in psychomotor assessment; most of the teachers less understand the elements of 4C; teachers find difficulty in arranging the criteria of learning completeness of learning purposes; the teachers do not give detail task to the students for the activity of 4C as the base of psychomotor assessment. In conclusion, this research states that there is less optimal teachers’ pedagogical competence in applying psychomotor assessment integrated with 4C, so it needs an application model for psychomotor assessment to improve teachers’ pedagogical competence integrated with 4C based on a database. Application based on technology is used for helping teachers to do psychomotor assessments in a valid, transparent, measurable, and well-documented way. Teachers’ pedagogical competence has impact on the improvement of learning quality and psychomotor learning outcomes.